Callus Induction of Ciangir Passion Fruit (Passiflora sp.) Leaves at Several Concentration Levels of Growth Regulators Substance 2,4-D and BAP - Putri, Salma Sasyana; Susiyanti; Muztahidin, Nur Iman; Isminingsih, Sulastri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Passion fruit plants are important economically due to the high nutrient value of the fruit, and they have an important role in the pharmaceutical world. People often exploit passion fruit plants for medicinal purposes without cultivating them. Passion fruit propagation can be done using seeds, grafting, or cuttings. However, such propagation can increase the value of high genetic variability so that to overcome this can be done by propagating passion fruit seedlings in tissue culture by callus induction. This research was carried out to determine the effect of 2,4-D and BAP on callus induction in passion fruit leaves. The method utilized was a factorial Randomized Group Design (RGD), which consisted of two factors, namely the 2,4-D concentration level (0, 1, 2, 3) ppm and the BAP concentration level (0, 1, 2) ppm, so there were 12 treatment combinations which were repeated three times. The observed parameters were callus area, percentage of browning explants, percentage of living explants, percentage of callus explants, color and texture of callus. The concentration level of 2,4-D 3 ppm and BAP 0 ppm best affected the callus area parameter of 1.96 . The results of this research showed that the percentage of the highest living explants achieved 100%, the percentage of contaminated explants was 0%, the percentage of explants that experienced browning was 66%, and the percentage of explants that experienced callus was 100%, yellowish green in color of callus, and callus texture is crumbly, compact, intermediate. The research should focus on callus induction with other growth regulators.